Pretargeted Nuclear Imaging and Radioimmunotherapy Based on the Inverse Electron-Demand Diels–Alder Reaction and Key Factors in the Pretargeted Synthetic Design. (25th August 2019) - Qiu, Lin; Mao, Wujian; Yin, Hongyan; Tan, Hui; Cheng, Dengfeng; Shi, Hongcheng
Abstract : The exceptional speed and biorthogonality of the inverse electron-demand Diels–Alder (IEDDA) click chemistry between 1, 2, 4, 5-tetrazines and strained alkene dienophiles have made it promising in the realm of pretargeted imaging and therapy. During the past 10 years, the IEDDA-pretargeted strategies have been tested and have already proven capable of producing images with high tumor-to-background ratios and improving therapeutic effect. This review will focus on recent applications of click chemistry ligations in the pretargeted imaging studies of single photon emission computed tomography (SPECT), positron emission tomography (PET), and pretargeted radioimmunotherapy investigations. Additionally, the influence factors of stability, reactivity, and pharmacokinetic properties of TCO tag modified immunoconjugates and radiolabeled Tz derivatives were also summarized in this article, which should be carefully considered in the system design in order to develop a successful pretargeted methodology. We hope that this review will not only equip readers with a knowledge of pretargeted methodology based on IEDDA click chemistry but also inspire synthetic chemists and radiochemists to develop pretargeted radiopharmaceutical components in a more innovative way with various influence factors considered.